Enhancing Trust Between PPP Partners: The Role of Contractual Functions and Information Transparency. (August 2021) - Cheng, Mengyuan; Liu, Guoliang; Xu, Yongshun; Chi, Ming
Contracts are essential for managing the relationship among public–private partnership (PPP) partners. However, the impact of contracts on the trust between partners is unclear, especially in PPP projects. From the multifunctional perspective of contracts, this study aims to investigate how different dimensions of contractual functions affect distinct types of trust and the moderating role of information transparency between them. The empirical results of the data collected from Chinese PPP professionals show that the three dimensions of contractual functions have positive effects on trust, including goodwill trust and competence trust. However, contractual adaptation has the strongest impact. Moreover, information transparency positively moderates the relationship between contractual control, adaptation, and trust. This study provides new insights on contracts and trust in PPP projects. It can guide PPP project partners to value the process of contract design and information disclosure to cultivate specific types of trust.